El Excentrico, 1966-10-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
October 20, 1966 [5 de octubre de 1966]. No volume or issue number. Cover has a photograph of Angie Medina in Halloween costume. The headline reads, "Angie Medina witching you a witchy Halloween."